A Diverse Assembly The Debate on a Scottish Parliament - Paterson, Lindsay (Edinburgh University Press, 2022)
The 1997 Scottish Referendum confirmed the wish of the people of Scotland for their first Parliament in almost 300 years. In A Diverse Assembly Lindsay Paterson draws together for the first time a collection of the key arguments for and against the reinstating of a Scottish Parliament. Gathered from newspapers, journals, books and speeches, the voices of the major players in the debate can be heard.Key FeaturesThe only collection of its kind: allows the reader to trace the arguments behind the debate on a Scottish ParliamentStrong representation of the main viewpoints in the debate and of the four main political parties in ScotlandIncludes the words of many of the key figures in politics including Edward Heath, John Smith, Robin Cook and Margaret Thatcher